Instruments for the identification of patients in need of palliative care in the hospital setting: a systematic review of measurement properties. Issue 3 (22nd March 2022) - Teike Lüthi, Fabienne; MacDonald, Ibo; Rosselet Amoussou, Joëlle; Bernard, Mathieu; Borasio, Gian Domenico; Ramelet, Anne-Sylvie
ABSTRACT: Objective: The objective of this review was to provide a comprehensive overview of the measurement properties of the available instruments used by clinicians for identifying adults in need of general or specialized palliative care in hospital settings. Introduction: Identification of patients in need of palliative care has been recognized as an area where many health care professionals need guidance. Differentiating between patients who require general palliative care and patients with more complex conditions who need specialized palliative care is particularly challenging. Inclusion criteria: We included development and validation studies that reported on measurement properties (eg, content validity, reliability, or responsiveness) of instruments used by clinicians for identifying adult patients (>18 years and older) in need of palliative care in hospital settings. Methods: Studies published until March 2020 were searched in four databases: Embase.com, MEDLINE (Ovid), PubMed, and CINAHL (EBSCO). Unpublished studies were searched in Google Scholar, government websites, hospice websites, the Library Network of Western Switzerland, and WorldCat. The search was not restricted by language; however, only studies published in English or French were eligible for inclusion. The title and abstracts of the studies were screened by two independent reviewers against the inclusion criteria. Full-text studies were reviewed for inclusion by two independent reviewers. The quality of the measurement properties of all included studies were assessed independently by two reviewers according to the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) methodology. Results: Out of the 23 instruments identified, four instruments were included, as reported in six studies: the Center to Advance Palliative Care (CAPC) criteria, the Necesidades Paliativas (NECPAL), the Palliative Care Screening Tool (PCST), and the Supportive and Palliative Care Indicators Tool (SPICT). The overall psychometric quality of all four instruments was insufficient according to the COSMIN criteria, with the main deficit being poor construct description during development. Conclusions: For the early identification of patients needing palliative care in hospital settings, there is poor quality and incomplete evidence according to the COSMIN criteria for the four available instruments. This review highlights the need for further development of the construct being measured. This may be done by conducting additional studies on these instruments or by developing a new instrument for the identification of patients in need of palliative care that addresses the current gaps in construct and structural validity. Systematic review registration number: PROSPERO CRD42020150074